The effect of feeding mixtures of banana trunk and soybean meal on lambs performance - I-W Mathius; D Yulistiani; w Puastuti; M Martawidjaja (Indonesian Center for Animal Research and Development (ICARD), 2001)
This study was intended to determine the effects of increasing the ratio of banana trunk to soybean meal on intake, nitrogen excretion and lambs performance. Sixteen lambs (averaging 21.21 + 1.69 kg) were pen individually and fed a basal diet consisted of chopped fresh king grass and commercial concentrate and unlimited access of water. Lambs were randomly assigned to one out of four different ratio of banana trunk to soybean meal as feed supplements, i.e. (R0) 0:1; (R1) 1:1; (R2) 2:1 and (R3) 4:1. Results showed that the inclusion of banana trunk had no adverse effect on lambs performance. As it is expected, altering the ratio of banana trunk to soybean meal increased (P < 0.05) dry matter intake of forage as well as total dry matter intake. The digestion coefficient of dietary ration was not affected (P >0.05) by feed supplement. Despite of no difference was observed in the coefficient of nitrogen digestibility, apparent fecal and urine N-output were significantly (P < 0.05) affected. The highest ratio of fed supplement (R3) tended to decrease nitrogen retention. Overall data indicated that lambs offered basal diet supplemented with R2 treatment accumulated more N per-day, than those fed other treatments, and consequently lambs performance was the best on those fed R2 treatment. Key words: Banana trunk, protected protein, lambs